# Algebra

posted by .

Given f(x)= 2x^2 – 1 and g(x) = –2x + 1, find the following.
f(3) − g(3)

• Algebra -

f(3) - g(3)
= 2(3^2) - 1 - (-2(3) + 1)
= 18-1 - (-5)
= 23

## Similar Questions

1. ### algebra

Which of the following is equivalent to the expression (t2 − t − 6)(t − 3)−1 ?
2. ### biology

Given the part of the molecule shown below, can the underlined atom participate in a hydrogen bond with an approriate bonding partner?
3. ### Algebra

Please help I can't figure out these two. Express f(x) in the form a(x − h)2 + k. f(x) = −4x2 + 24x − 9 Find the standard equation of a parabola that has a vertical axis and satisfies the given conditions. vertex …

Evaluate each of the following. Show all your calculations. a) f'(3) if f(x)  = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X)  = −3x^2 − 5x + 7 …
5. ### calculus (gr 12)

Evaluate each of the following. Show all your calculations. a) f'(3) if f(x)  = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X)  = −3x^2 − 5x + 7 …
6. ### Algebra

Given f(x)=2x^2 + 9x − 7and g(x)=2x −6, find the following. (If an answer is undefined, enter UNDEFINED.) f(−2) − g(−2)
7. ### Alg.

Given g(x) = x^2 – 3, find the following. g(−4 + h) − g(−4)/ h (all over h)
8. ### Alg

Given f(x) = 2x^2 – 2 and g(x) = –2x + 4, find the following. (f − g)(2) AND Given f(x) = 2x − 2 and g(x) = 4x − 5, evaluate the composite function. f[g(2)]
9. ### linear algebra

If possible, find an example of actual numbers c1, c2, and c3, not all zero, so that the following is true. c1[3,3,−1] + c2[1,2,−3] + c3[−11,−13,9] = [0,0,0]
10. ### Algebra 1

Evaluate the following expression using the values given: Find 3x^2 − y^3 − y^3 − z if x = 3, y = −2, and z = −5. Numerical Answers Expected! thanks so much if you could help me. This is for an exam and …

More Similar Questions